1963
DOI: 10.1126/science.141.3577.272
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Penetration of Wheat Seedlings by Stem and Leaf Rust: Effect of Light and Carbon Dioxide

Abstract: Removal of atmospheric carbon dioxide enhanced penetration of seedling wheat by stem rust Puccinia graminis in light and dark but did not materially affect penetration by leaf rust P. recondita. A concentration of 5 percent CO(2) nearly suppressed penetration by P. graminis but not by P. recondita. Thus light may promote penetration by P. graminis through photosynthetic reduction of CO(2) within the leaf and P. recondita may penetrate independently of light because it is relatively insensitive to the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

1964
1964
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 0 publications
1
16
0
4
Order By: Relevance
“…According to our histological analysis in Bd1-1 (Figure 4), the growth of Pg-tr , Pg-lo and Pg-pp in Brachypodium during the first 12 hpi (under dark, wet conditions) is comparable to that of Pg-tr in susceptible or resistant wheat cultivars [16]. Under comparable experimental conditions, the formation of substomatal vesicles and primary hyphae of Pg-lo and Pg-pp follow a time course similar to that reported in compatible and incompatible interactions between Pg-tr and wheat [16], [17], [18], [19] or barley [59], [60]. However, compared to Pg-tr in its natural hosts, Pg-lo and Pg-pp in Brachypodium display a delay in the formation of first haustoria (16 to 20 hpi in wheat and 18 hpi in barley vs. 32 hpi in Brachypodium ) [16], [60] and emergence of secondary infection hyphae (24 to 36 hpi in wheat and barley vs. 42 hpi in Brachypodium ) [16], [17], [60].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…According to our histological analysis in Bd1-1 (Figure 4), the growth of Pg-tr , Pg-lo and Pg-pp in Brachypodium during the first 12 hpi (under dark, wet conditions) is comparable to that of Pg-tr in susceptible or resistant wheat cultivars [16]. Under comparable experimental conditions, the formation of substomatal vesicles and primary hyphae of Pg-lo and Pg-pp follow a time course similar to that reported in compatible and incompatible interactions between Pg-tr and wheat [16], [17], [18], [19] or barley [59], [60]. However, compared to Pg-tr in its natural hosts, Pg-lo and Pg-pp in Brachypodium display a delay in the formation of first haustoria (16 to 20 hpi in wheat and 18 hpi in barley vs. 32 hpi in Brachypodium ) [16], [60] and emergence of secondary infection hyphae (24 to 36 hpi in wheat and barley vs. 42 hpi in Brachypodium ) [16], [17], [60].…”
Section: Discussionsupporting
confidence: 72%
“…The formation of appressoria can be detected at 6 hpi [17] and maximum appressorium development is reached by 12 hpi [16]. Subsequent to appressorium formation, light and photosynthesis-associated O 2 reduction stimulate the growth of a penetration peg and a substomatal vesicle in the mesophyll space [18]. Substomatal vesicles form within 1.5 h after light exposure [19] and a primary infection hypha emerges from the vesicle, and eventually differentiates a haustorial mother cell.…”
Section: Introductionmentioning
confidence: 99%
“…Uredinial infection was later found to follow the ecological distribution and the rapid global expansion of perennial ryegrass cultivation (Potter et al, 1990). Following contact with a stoma, a germ-tube ceases to elongate and forms an appressorium over the stoma (Yirgou and Caldwell, 1968). In contrast to cereal leaves, ryegrass leaves have few stomata on the abaxial surface, dramatically reducing the incidence of infection.…”
Section: Biology Of the Crown Rust Pathogen Of Ryegrasses First Obsermentioning
confidence: 99%
“…This resumption of development probably depends only indirectly on light through its stimulation of photosynthesis and reduction of CO 2 concentration at stomata in the host plant. Yirgou and Caldwell (1968) showed that penetration of the host by P. graminis is inhibited by CO 2 but will occur nearly equally well in light or dark in CO 2 ‐free air. Penetration by appressoria of P. graminis did not occur on non‐photosynthetic albino wheat plants or etiolated plants in 1% ambient CO 2 .…”
Section: Infection Processmentioning
confidence: 99%